IMPLIKASI R-WALL UNTUK PENDETEKSIAN DAN PENGAMANAN SERANGAN SIBER PADA SERVER - Abdul Djalil Djayali; Rifaldi Nurdin; Rachmat Saleh Sukur (Universitas Nusa Cendana, 2021)
Security is inversely proportional to comfort, the more comfortable the application of technology will have an impact on the security side of the system. The Server is an important infrastructure in managing data. It is important to prevent attacks on Servers. Firewall implementation can minimize attacks that harm the Server. One of them is by implementing an Intrusion Detection System (IDS) application such as Snort which has the ability to detect attacks that occur on Server systems. In this study, the authors developed a system called R-Wall. The implementation of R-Wall aims to be able to monitor and secure Servers against several attack methods, including port scanning, DDoS ping of death SSH brute force, and FTP brute force type. The results of this implementation are able to provide attack notifications sent via Telegram robot with a total of 247 DDoS pings of deadly attacks, 8 port scanning attacks, 247 FTP brute force attacks, and 208 SSH brute force attacks. R-Wall is also able to restrict access to attackers.